Intertemporal Labor Supply and Long-Term Employment Contracts - Abowd, John M.; Card, David (American Economic Review, 1987)
[We compare a contracting model and a labor supply model. One test is whether earnings changes are more variable than hours changes, as predicted by the labor supply model, or less variable, as predicted by the contracting model. We apply this test to two longitudinal surveys and find that earnings are somewhat more variable than hours for men who never change employers. The estimates suggest that changes in earnings and hours not associated with measurement error occur at fixed wage rates.]